(untitled) (Rajshahi University Journal of Life & Earth and Agricultural Sciences, 2015)
Root characters, leaf yield and yield components of five mulberry varieties in relation to soil moisture i.e. well-watered, water- stress and water logging was studied in pot condition. Lower root length with higher dry weight were observed in the well-watered plants, on the other hand, shorter root length with lower dry weight was in the waterlogged plants compared to the water-stressed plants. Wellwatered plants had the highest, water-stressed plants had the lowest and waterlogged plants had the intermediate values for plant height and fresh stem weight. All the leaves of the waterlogged plants were shed at 90 days after planting. The water-stressed plants had higher shoot-root ratio followed by the well-water and waterlogged plants.